DNA mismatch repair and the DNA damage response - Li, Zhongdao (DNA Repair (Amst), 2015)
This review discusses the role of DNA mismatch repair (MMR) in the DNA damage response (DDR) that triggers cell cycle arrest and, in some cases, apoptosis. Although the focus is on findings from mammalian cells, much has been learned from studies in other organisms including bacteria and yeast [1,2]. MMR promotes a DDR mediated by a key signaling kinase, ATM and Rad3-related (ATR), in response to various types of DNA damage including some encountered in widely used chemotherapy regimes. An introduction to the DDR mediated by ATR reveals its immense complexity and highlights the many biological and mechanistic questions that remain. Recent findings and future directions are highlighted.